The good earth [videorecording (DVD)] - Franklin, Sidney A., 1893-1972; Muni, Paul, 1895-1967; Rainer, Luise, 1910-2014; Connolly, Walter, 1887-1940; Stothart, Herbert, 1885-1949; Buck, Pearl S. (Pearl Sydenstricker), 1892-1973 (Distributed by Warner Home Video, 2006)
A young farmer named Wang Lung marries a selfless, loyal slave girl, O-Lan. Wang is initially devoted to the land and rises to prosperity. Later, however, Wang deserts the land and takes a second wife and tragedy threatens to overwhelm him. Eventually Wang realizes that the land and O-Lan mean more to him than his wealth.